Pengembangan Multimedia Biologi pada Materi Sistem Pencernaan Manusia Berbasis Macromedia Flash untuk Siswa Kelas VIII SMP - Handra Anwar; Damris Damris; Upik Yelianti (Universitas Jambi, 2017)
Abstract Good multimedia is a simple and easy to understand so it can be a tool to increasing the interest of students especially in subject that required visualization. This research aim to develope the interactive learning multimedia using Macromedia Flash for students grade VIII human digestive system subject. The model used in this research is ADDIE developing model. The ADDIE developing model have some procedure such as Analyze, Design, Development, Implementation and Evaluation.The result of this research is a product of Biology learning Multimedia designed by Macromedia Flash and developed under ADDIE model. Developing proccess have some shortages. From validation step, media expert given the shortage from text, communicative powe, practice test and narrator voice with score 50 and 66,7% (phase I) and in phase II 71 and 94,7%. Content expert found that acontent is not complete, description picture still not clear and leak of practice test with score in phase I, II and III are 33 (60%), 40 (72,7%) and 47 (85,5%). In field test, most of students and teachers response found that product deserves to be used in classroom with score percentage for small group, large group and teachers are 95,2%, 85,6% dan 80%.